Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Pra Lansia Tentang Komplikasi Diabetes Mellitus di Poli Penyakit dalam RSUD Palangka Raya - Lenny Frilly Siagian; Karmitasari Yanra Katimenta; Meilitha Carolina; Septian Mugi Rahayu (PPNI UNIMMAN, 2024)
Steps to optimize treatment adherence and care are implemented through health education for patients. Health education is crucial because Diabetes Mellitus is a lifestyle-related disease, necessitating increased knowledge. In the research location, it was found that pre-elderly individuals diagnosed with Diabetes Mellitus were routinely undergoing treatment, but their blood sugar levels remained unstable. Additionally, they rarely engaged in physical activity, their Diabetes Mellitus diet was uncontrolled, and they often did not regularly take diabetes medication. If left unaddressed, this could lead to complications. The objective of this study is to analyze the effect of health education on the knowledge of pre-elderly individuals about Diabetes Mellitus complications at the internal medicine clinic of Palangka Raya General Hospital. Method: This study used a Pre-Experimental design with a one-group pre- and post-test approach. The sampling technique was purposive sampling, with 60 respondents. Results: Based on the Wilcoxon test results, a p-value of 0.000 was obtained, indicating a significance level of p < 0.05, meaning Ha was accepted. This shows that there is an effect of health education on the knowledge of pre-elderly individuals regarding Diabetes Mellitus complications at the internal medicine clinic of Palangka Raya General Hospital. Conclusion: There is an effect of health education on the knowledge of pre-elderly individuals about Diabetes Mellitus complications. This study can be used as a source of information and to establish a counseling corner for providing health education on a weekly basis.